The Impact of Music Education on the Development of Cognitive and Emotional Skills in Children: A Study on Piano Teaching Methods - Sokolova Fotima Kamilovna (Researchparks Publishing, 2023)
This research investigates the influence of different piano teaching methods on the cognitive functions, including memory, attention, and creative thinking, as well as the emotional state of children. The study aims to shed light on the role of music education, specifically piano instruction, in enhancing children's cognitive abilities and emotional well-being. Various teaching techniques and their effects on children's cognitive and emotional development are analyzed, providing valuable insights into the optimization of music education programs.